DESIGN OF AYOPANEN APPLICATION FOR MANAGEMENT OF AGRICULTURAL PRODUCT PROVIDERS - Prasetyo, Wildan Harits; Eko Wulandari, Sri Hariani; Ningsih, Norma (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Ayopanen is an application that moves as a market place for the sale of agricultural products. Ayopanen bridges between farmers as product providers and buyers as product enthusiasts. Farmers who usually make sales through long distribution channels now only need to make sales through the application. This makes farmers more profitable because of shorter distribution channels and customers benefit from cheaper prices. The solution is to build an application that can be used to manage product data, manage price data and create reports Ayopanen System. With this feature farmers can start transaction activities smoothly on Ayopanen so as to provide benefits for both parties both farmers and buyers. Management of pricing data in Ayopanen is the management of lower and upper price data for each product. The upper price is obtained from the current market price and the bottom price is obtained using 2 methods of mark up pricing obtained after entering the cost of production of each product and peak load pricing obtained from existing sales and stock transactions in Ayopanen. The results of trials and evaluations that have been done indicate that the application can help farmers in managing the product, providing price advice as a reference in determining the price, then can provide reports in the form of sales reports and product rating reports